Zamaskování pohybujícího se objektu ve videu - Dostál, Martin (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2012)
Hiding moving objects in video sequences is an interesting topic in computer vision. In this thesis, a real-time single object tracking and removal method is proposed. An input video is assumed to be captured with static video camera. Motion detection is based on a background subtraction using Mixture of Gaussians as the representation of background. The object tracking is realized by a combination of blobs comparison and computation of optical flow using Lucas-Kanade method. Consequent object removal makes use of created background model.
Keywords: počítačové vidění; object tracking; moving object removal; OpenCV; computer vision; sledování objektu; maskování pohyblivého objektu; motion detection; detekce pohybu